PENGELOLAAN SAMPAH RUMAH TANGGA DI DUKUH KUNCEN SIDODADI DELANGGU - LMS Kristiyanti; Rukmini Rukmini; Wikan Budi Utami; Maya Widyana Dewi (LPPM ITB AAS Indonesia Surakarta, 2020)
This service activity was carried out with the background of wanting to help the Sido Bersinar Self-Help Group (KSM) in Kuncen Sidodadi Delanggu hamlet in managing household waste. The purpose of this community service is to provide motivation on how to improve the performance of KSM based on TPS 3R (Waste Reduce Reuse Recycle) by utilizing local village personnel and motivating local people to use used goods into products that are ready to be sold to increase family income. Community service activities are carried out using the lecture method to socialize the activities of KSM Sido Bersinar Delanggu. The expected output target of this activity is that KSM is able to increase production and sales of business activities that have been initiated so that they can develop and be able to improve the standard of living of the people of Delanggu village.This service activity was carried out with the background of wanting to help the Sido Bersinar Self-Help Group (KSM) in Kuncen Sidodadi Delanggu hamlet in managing household waste. The purpose of this community service is to provide motivation on how to improve the performance of KSM based on TPS 3R (Waste Reduce Reuse Recycle) by utilizing local village personnel and motivating local people to use used goods into products that are ready to be sold to increase family income. Community service activities are carried out using the lecture method to socialize the activities of KSM Sido Bersinar Delanggu. The expected output target of this activity is that KSM is able to increase production and sales of business activities that have been initiated so that they can develop and be able to improve the standard of living of the people of Delanggu village. Keywords: Waste management, increased production